(untitled) (Konturen, 2013)
Beginning with an analysis of certain tone-row partitions in Schoenberg’s opera Moses and Aaron, this article examines the ways in which the composer dramatized the conflict between the two Biblical brothers by setting leitmotifs in opposition, conveying the tension (between the visual and verbal portrayal of God) in terms of an abstract, symmetrical system.